Time-resolved resonance raman and time-resolved step-scan FTIR studies of nitric oxide reductase from paracoccus denitrificans: comparison of the heme b3-FeB site to that of the heme-CuB in oxidases - Pinakoulaki, Eftychia; Varotsis, Constantinos (My University, 2003)
Time-resolved resonance Raman (TR3) and time-resolved step-scan (TRS2) FTIR spectroscopies have been used to probe the structural dynamics at the heme b3 proximal and distal sites after carbon monoxide photolysis from fully reduced CO-bound nitric oxide reductase. The Raman spectra of the transient species exhibit structural differences relative to the equilibrium geometry of heme b3. The most significant of these is a shift of 8 cm-1 to higher frequency of the 207 cm -1 mode, and a shift of 7 cm-1 to lower frequency of the ν4 mode. Our results indicate that the 207 cm-1 mode observed in the equilibrium-reduced heme b3 originates from ν(Fe-His). Its behavior in the photolytic transients indicates that the relaxed Fe-His state is not significantly populated. We suggest that relaxation along the tilt angle (θ) of the proximal histidine with respect to the heme plane and the out-of-plane displacement of the Fe (q) are coupled, and ligand binding and dissociation are accompanied by significant changes in the angular orientation of the His ligand. The results are compared to those obtained for the aa3-cytochrome c oxidase from Paracoccus denitrificans. The results are compared to those obtained for the aa 3-cytochrome c oxidase from P. denitrificans. The TR3 and TRS2 FTIR data demonstrate significant alterations in the nature of the heme-protein dynamics between nitric oxide reductase and heme-copper oxidases resulting from specific structural differences in their respective hemepockets
Keywords: Enzymes; Carbon monoxide; Dissociation; Fourier transform infrared spectroscopy; Nitrogen oxides; Raman spectroscopy; Heme; Copper; Molecular dynamics; Spectrum analysis